Peran Metode Peer Teachiing dalam Pengembangan Kemampuan Mahasiswa pada Mata Kuliah Pembinaan Kompetensi Mengajar - Puput Puspitorini (Edumaspul: Jurnal Pendidikan, 2022)
Responding to the implications of the challenges of the world of education, the duties and functions of lecturers in the future will be more complex so that it requires continuous coaching and adjustment of competencies. Peer teaching is one of the most effective learning methods. This research aims to describe the Role of Peer Teaching Methods in the Development of Student Abilities in Teaching Competency Development Courses. This research was conducted using descriptive qualitative methods. The results of the study showed that by using a peer-teaching model, lecturers could choose a suitable strategy, based on the material to be discussed. Especially in terms of developing students' abilities in teaching competency coaching courses